LINGKUNGAN PENGENDAPAN BATUBARA, FORMASI KALUMPANG DI DAERAH MAMUJU - Moh Heri Hermiyanto; Sahril Andi Mangga; Koesnama Koesnama (Jurnal Geologi dan Sumberdaya Mineral, 2010)
Kalumpang (Toraja) Formation comprises syn-rifting sediments of Middle Eocene – Late Eocene age. This formation consists of quartz sandstone, conglomerate, shale, claystone with alternations of coal and limestone. Geochemical analysis shows that the caloric value ranges from 2480 kal/gr to 7440 kal/gr, moisture varies from 1,3%-6,7%, volatile matter 14,7%-44,9%, total sulphur 0,82%-7,70%, and the specific gravity ranges from 1,33 to 2,17. Based on the organic petrography analysis, the coal contains vitrinite 91,6 – 100%, liptinite or exinite 0,1 – 8,2 %,and inertinite 0,1 – 1 %. Maximum reflectance vitrinite (Rv-max) is ranging from 0,32%-0,62%, Ro 47%. The dominant maceral group is vitrinite, with rare liptinite. The high content of vitrinite suggests that the coal in Kalumpang is derived from plants in humic condition which were deposited in wet forest swamp. Meanwhile, the low content of inertinite indicates that oxidation processes did not take place intensely.Keywords : Kalumpang Formation, coal, eocene, organic petrology, maceral